1995
DOI: 10.1111/j.1095-8649.1995.tb06006.x
|View full text |Cite
|
Sign up to set email alerts
|

Size structure, sex ratio and onset of sexual maturity of two species of Hypostomus

Abstract: Length-frequency analyses showed that male HypostomuS ufinis are bigger than femalcs, but H. luetkeni showed no such differences. The sex ratio was estimated at 1 : 1 for both species.The temporal variation of sex ratio indicated a decrease in the male population when GSI was at its maximum value, suggesting that males are less prone to capture during the spawning season. According to the decrease of males during the reproductive period, paternal behaviour is proposed for both species. H. ufinis reached sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
4
26
1
5
Order By: Relevance
“…Among the members of Loricariidae, the number of males was higher than the number of the females (Nomura and Mueller, 1980;Bruschi-Jr. et al, 1997), but there were some exceptions (Barbieri and Santos, 1987). Non-significant differences in sex rate for Loricariidae were found by Antoniutti et al, (1985) and Mazzoni and Caramaschi (1995). Several factors can influence sex rate: growth rates influence Plecostomus albopunctatus (Antoniutti et al, 1985); mortality rates influence H. affinis and Hypostomus luetkeni (Mazzoni and Caramaschi, 1997); differences on behavior between males and females or selective capture influence Pseudocurimata gilberti (Honda, 1979apud Antoniutti et al, 1985; and partial segregation by sex influences Oligosarcus jenynsii (Hartz et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…Among the members of Loricariidae, the number of males was higher than the number of the females (Nomura and Mueller, 1980;Bruschi-Jr. et al, 1997), but there were some exceptions (Barbieri and Santos, 1987). Non-significant differences in sex rate for Loricariidae were found by Antoniutti et al, (1985) and Mazzoni and Caramaschi (1995). Several factors can influence sex rate: growth rates influence Plecostomus albopunctatus (Antoniutti et al, 1985); mortality rates influence H. affinis and Hypostomus luetkeni (Mazzoni and Caramaschi, 1997); differences on behavior between males and females or selective capture influence Pseudocurimata gilberti (Honda, 1979apud Antoniutti et al, 1985; and partial segregation by sex influences Oligosarcus jenynsii (Hartz et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…Em setembro, ocorreu um deslocamento da distribuição da largura dos folículos para larguras intermediárias e em dezembro, observa-se que a freqüência relativa da largura dos folículos distribui-se tanto em larguras menores quanto intermediárias e máximas (Figs 6 e 7). Assim, a análise da distribuição de freqüência da largura dos folículos ovarianos sugere que a desova de M. sanctaefilomenae é Quando a proporção esperada não ocorre, fatores como predação e variação nas condições ambientais locais podem estar envolvidos (MAZZONI & CARAMASCHI 1995, RAPOSO & GURGEL 2001, GARCIA et al 2004. As diferenças na proporção sexual podem ser atribuídas a elevada taxa de mortalidade de fêmeas como resultado da sucetibilidade a predação (MAZZONI & CARAMASCHI 1995).…”
Section: Resultsunclassified
“…Assim, a análise da distribuição de freqüência da largura dos folículos ovarianos sugere que a desova de M. sanctaefilomenae é Quando a proporção esperada não ocorre, fatores como predação e variação nas condições ambientais locais podem estar envolvidos (MAZZONI & CARAMASCHI 1995, RAPOSO & GURGEL 2001, GARCIA et al 2004. As diferenças na proporção sexual podem ser atribuídas a elevada taxa de mortalidade de fêmeas como resultado da sucetibilidade a predação (MAZZONI & CARAMASCHI 1995). O tamanho, a coloração e a atividade natatória dos machos de gupies Poecilia reticulata (Peters, 1859) aumentam a probabilidade destes serem predados (RODD & REZNICK 1997).…”
Section: Resultsunclassified
“…Many studies concerning Loricariidae (e.g. Hypostomus) behaviour have shown that they usually explore small stream stretches, mainly during the breeding season (Mazzoni, Caramaschi, 1995), suggesting that they did not move long distances from their territories. Nonetheless, the ability to move is a necessary prerogative for species to disperse and colonize new habitats (Hohausová et al, 2010).…”
Section: Discussionmentioning
confidence: 99%